Gobierno electrónico y la calidad de servicio en el Gobierno Regional de Loreto, 2020 - Dávila Vargas, Luis Orlando (2022)
The main objective of this study was to establish the relationship between electronic government and quality of service in the Regional Government of Loreto, 2020, being a descriptive-correlational study with a non-experimental design; taking into account a sample of 149 workers from a population of 248, for which the survey technique has been used and the questionnaire created from the dimensions and indicators of each variable has been used as an instrument; procedure and data analysis that leads to conclude the following: that the development of electronic government has been running poorly, since the GORE Loreto website is not updated information or published in different formats (flyers, news, videos) Likewise, the web platform is not easy for them to use. Lastly, the online service provided by the Regional Government of Loreto is not always transparent. The level of quality of service is low, because the online service is almost never useful for the user, likewise, it is not possible to carry out procedures at any time of the day, the procedures carried out are not attended to quickly and are never used. of modern technology such a platform. In general terms, it was determined that there is a significant relationship between electronic government and the quality of service in Gore Loreto, compared to 2020, this has been contrasted with a significance of 0.000 and a correlation coefficient of 0.870 which is positive high.